2013
DOI: 10.2139/ssrn.2326705
|View full text |Cite
|
Sign up to set email alerts
|

Politics 2.0: The Multifaceted Effect of Broadband Internet on Political Participation

Abstract: We investigate the causal impact of broadband Internet on political participation using data from Italy. We show that this impact varies across different forms of political engagement and over time. Initially, broadband had a negative effect on turnout in national elections, driven by increased abstention of ideologically extreme voters. Meanwhile, however, broadband fostered other forms of online and offline participation. Over time, the negative effect was reverted due to the emergence of new political entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 39 publications
2
93
0
Order By: Relevance
“…I have noted that there is strong empirical evidence that a quantitatively significant fraction of voters switch away from leading candidates in the UK (Franklin et al ., ) and the US (Burden, ). There is further evidence for many other countries including Austria, Denmark, Italy, Norway, Spain, Sweden and others (van der Brug et al ., ; Bergh, ; Erlingsson and Persson, ; Campante et al ., ; Superti, ).…”
Section: Related Literaturementioning
confidence: 97%
“…I have noted that there is strong empirical evidence that a quantitatively significant fraction of voters switch away from leading candidates in the UK (Franklin et al ., ) and the US (Burden, ). There is further evidence for many other countries including Austria, Denmark, Italy, Norway, Spain, Sweden and others (van der Brug et al ., ; Bergh, ; Erlingsson and Persson, ; Campante et al ., ; Superti, ).…”
Section: Related Literaturementioning
confidence: 97%
“…In addition, the available surveys do not reveal the kind of interaction users actually experience in SNS. Economic studies relying on survey data basically analyze how certain behaviors correlate to binary variables measuring broadband access ( Bauernschuster et al, 2014;Falck et al, 2014;Campante et al, 2017 ) and Internet or SNS use ( Pénard et al, 2013;Castellacci and Schwabe, 2017;Sabatini and Sarracino, 2017;Castellacci and Tveito, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our theory as well as the anecdotal evidence presented in Section 2 suggest that the Russian government strategically used state-controlled media to generate political support, by reminding the Russian population about the political and economic chaos during the years before Putin came to power. A sizeable literature has shown that the media can indeed significantly affect voting behavior ( (Campante, Durante, Sobbrio, 2017). In our paper, we build on this literature by providing further evidence that pro-government media content and state-control over the media can generate political support for the ruling party.…”
Section: Mechanismsmentioning
confidence: 82%